Validation of Babesia proteasome as a drug target - Jalovecka, Marie; Hartmann, David; Miyamoto, Yukiko; Eckmann, Lars; Hajdusek, Ondrej; O'Donoghue, Anthony J; Sojka, Daniel (International journal for parasitology. Drugs and drug resistance, 2018)
Babesiosis is a tick-transmitted zoonosis caused by apicomplexan parasites of the genus Babesia. Treatment of this emerging malaria-related disease has relied on antimalarial drugs and antibiotics. The proteasome of Plasmodium, the causative agent of malaria, has recently been validated as a target for anti-malarial drug development and therefore, in this study, we investigated the effect of epoxyketone (carfilzomib, ONX-0914 and epoxomicin) and boronic acid (bortezomib and ixazomib) proteasome inhibitors on the growth and survival of Babesia. Testing the compounds against Babesia divergens ex vivo revealed suppressive effects on parasite growth with activity that was higher than the cytotoxic effects on a non-transformed mouse macrophage cell line. Furthermore, we showed that the most-effective compound, carfilzomib, significantly reduces parasite multiplication in a Babesia microti infected mouse model without noticeable adverse effects. In addition, treatment with carfilzomib lead to an ex vivo and in vivo decrease in proteasome activity and accumulation of polyubiquitinated proteins compared to untreated control. Overall, our results demonstrate that the Babesia proteasome is a valid target for drug development and warrants the design of potent and selective B. divergens proteasome inhibitors for the treatment of babesiosis.
Keywords: Cell Line; Babesia microti; Oligopeptides; Epoxyketone; Babesia; kyseliny boronové; Disease Models, Animal; Proteasome Endopeptidase Complex; Proteasome Inhibitors; oligopeptidy; Proteasome; Mice; lékové transportní systémy; proteasomový endopeptidasový komplex; Cytotoxicity; Macrophages; Babesiosis; modely nemocí na zvířatech; ženské pohlaví; Proteome; Carfilzomib; zvířata; inhibitory proteasomu; babezióza; myši; makrofágy; buněčné linie; proteom; Drug Delivery Systems; Female; Boronic Acids; Animals